Evaluation of Contrast-enhanced Transcranial Color-coded Duplex Sonography (CE-TCCD) Applied in Stroke Patients with Intracranial Collateral Circulation - Xing, Jin; Xu, Bin; Zhai, Lin; Men, Yan; Zhang, Dan; Zhang, Wenjing; Cui, Jian (Current Medical Imaging, 2020)
Background and Introduction: Collateral circulation is very crucial for the prognosis of stroke patients. Transcranial color-coded duplexsonography (TCCD) is used widely to evaluate the intracranial arterial blood flow. However, approximately 20% - 30% of the patients with cerebral infarction cannot be detected via TCCD due to the interruption of thickened temporal bones. We assessed the diagnostic efficacy of contrast-enhanced transcranial color-coded duplexsonography (CE-TCCD) in stroke patients with limited bone windows. Methods: CE-TCCD was applied to 70 patients (51 males and 19 females) who presented with ischemic symptoms, to detect the openness of the anterior communicating artery (ACoA) and posterior communicating artery (PCoA) of the Willis ring before Computed Tomography angiography (CTA) or Magnetic Resonance Angiography (MRA) examination. The results from CETCCD is used to compare with CTA/MRA result to verify the diagnostic efficacy. Results: Forty-one communicating artery openings were detected by CE-TCCD, among which 37 were PCoA and 4 were ACoA. Among the 70 patients, 23 of 70 patients indicated severe stenosis within intracranial and/or extracranial arteries. Eighteen out of the 23 patients showed collateral circulation, accounting for 78.3% (18/23). Moderate stenosis were 23 cases in total, in which 7 cases showed collateral circulation, accounting for 30.4% (7/23). Slight stenosis were 24 cases in total, none of which showed collateral circulation. Conclusion: In the stroke patients with limited bone windows, CE-TCCD can evaluate intracranial collateral circulation.
Keywords: cerebral ischemia